Physical education: reducing stress and perfectionism in primary education: Stress and perfectionism in primary education - Castellanos Vega, Reina; Dinu, Elena Raluca (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Perfectionism is the personal requirement, evaluating its own value in terms of productivity and achievement. It uses an experimental methodology and has as main objective to know if the children of two years of fourth grade of primary are perfectionists and propose activities using the REAPSES method in the subject of physical education. In conclusion, thanks to the proposed activities the students/s claim to be more relaxed and with a clearer idea of the meaning of stress and how it affects them. However, in a way, some of the stress is caused by the level of demand from families.